Modular design of production systems tailored to regional market requirements: A Frugal Innovation perspective. Issue 11 (2018) - Belkadi, F.; Colledani, M.; Urgo, M.; Bernard, A.; Colombo, G.; Borzi, G.; Ascheri, A.
Abstract: Tailoring products for emerging regional markets under a frugal innovation perspective is a strategic opportunity for companies' competitiveness. However, this entails managing the co-evolution of adapted products and production systems for affordable manufacturing costs. In this paper, a modular design process is proposed to support the configuration of production systems adapted to regional market needs. It includes the matching of product and equipment modules, the line balancing, and the system design into an integrated problem. This modular approach supports the propagation of requirements in the product and system co-design process. The results are demonstrated in an automotive real case study.